2000
DOI: 10.1046/j.1365-2141.2000.02030.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased platelet activation and abnormal membrane glycoprotein content and redistribution in myeloproliferative disorders

Abstract: Summary. Chronic myeloproliferative disorders (MPDs) are characterized by a high incidence of thrombohaemorrhagic complications, possibly caused by platelet dysfunction. In an attempt to define platelet functional abnormalities, we assessed the expression of activation-dependent membrane proteins in unstimulated and agonist [ADP and thrombin receptor-activating peptide (TRAP)]-stimulated platelets using quantitative whole blood flow cytometry in samples from 50 MPD patients and 30 controls. The receptor densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 42 publications
8
95
1
3
Order By: Relevance
“…A propensity for thrombosis might be explained by an increased haematocrit level in polycythaemia vera and an inherent platelet activation as evidenced by abnormal eicosanoid metabolism, serological measurements of a-granule products, and spontaneous platelet aggregation [7À10]. In line with this, using whole blood¯ow cytometry we have recently demonstrated an increased platelet membrane expression of the a-granule proteins P-selectin and thrombospondin (TSP) in nonstimulated platelets of patients with MPD indicating increased granule secretion [11]. In addition, the expression of P-selectin and TSP positive platelets was positively correlated to the presence of plateletÀle-ukocyte aggregates [12].…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…A propensity for thrombosis might be explained by an increased haematocrit level in polycythaemia vera and an inherent platelet activation as evidenced by abnormal eicosanoid metabolism, serological measurements of a-granule products, and spontaneous platelet aggregation [7À10]. In line with this, using whole blood¯ow cytometry we have recently demonstrated an increased platelet membrane expression of the a-granule proteins P-selectin and thrombospondin (TSP) in nonstimulated platelets of patients with MPD indicating increased granule secretion [11]. In addition, the expression of P-selectin and TSP positive platelets was positively correlated to the presence of plateletÀle-ukocyte aggregates [12].…”
Section: Introductionmentioning
confidence: 79%
“…In the present study, we have evaluated the presence of risk markers for venous thromboembolism, ®brinolytic, and haemostatic system activation markers and antiphospholipid antibodies in a cohort of 50 patients with MPD and ascertained whether any marker of hypercoagulation or ®brinolysis was linked to the presence of activated platelets and plateletÀgranulocyte/monocyte aggregates [11,12]. Previous studies have indicated that in MPD activation of the coagulation system might be present as evidenced by elevations in prothrombin fragment 1+2 and ®-brinopeptide A levels [24À26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations